Legal Protection of Foreign Workers (TKA) in Indonesia - Arif Budiman Lubis; I Nyoman Budiana (Journal of Law, Politic and Humanities, 2025)
The primary objective of this study is to investigate the legal safeguards in place for foreign workers in Indonesia, also known as TKA. The study employed a normative legal research methodology, incorporating statutory, case-based, and conceptual approaches. Judges base their decisions on Article 62 of Labor Law Number 13 of 2003, ensuring that their rulings abide by the law to promote legal certainty and justice. Labor protection is a form of recognition of the rights of workers/laborers as human beings who must be treated humanely. In a country based on law (rechstaat), the mandate for the laws and regulations to be applied correctly is that judges must side with justice (moral justice).